National Constitutional Identity Confronted With the Constraints of European Union Law - Mathieu, Bertrand (Common Values and Constitutional Identities: Can Separate Gears Be Synchronised?, 2023)
This chapter considers some of the developments on national identity presented in a previous publication but focuses specifically on the analysis of the construction of a ‘European identity’ and the points of friction between these two types of identity.Constitutional identity corresponds to the essential elements of national identity a person has decided to include in its constitution, thus giving them legal scope. National identity enables the identification of a political community. This state community, formed by a people and endowed with the attribute of sovereignty, is defined by its history, values, and many elements that characterise its raison d’être and its specificity. Meanwhile, it is an element of separation from what is not it, an element of dialogue with other communities founded on other identity principles, and an element of sharing with other states that share some of the values in common.Considering the relationship between this national identity and the values of European identity, European identity, originally conceived as the common denominator of the values of national identities, developed in an almost autonomous manner through the affirmation of values forged by the Union’s bodies and, first, the Court of Justice of the European Union. Based on the common values enshrined in the Treaty, the Court will develop an extensive interpretation and definition of these values, in particular of the concept of the rule of law, which will allow it to extend its competences and enter into a federal logic that is not desired by the states. This identity, intended to be common and often imposed on the states, tends to achieve a European imperium that is not without ideological connotations.The resistance of several national jurisdictions to this imperium makes it necessary to seek mechanisms that allow for the promotion of common values and the protection of identity-based values. These mechanisms must restore the place of political power, which, in a democracy, has the greatest legitimacy to settle possible conflicts. The determination of new mechanisms of regulation between the requirements of the defence of national identities and those linked to the values and principles that sovereign states have decided to put in common, probably conditions for the survival of European legal orders.Keywords: constitutional identity, European identity, nation, values, European Union, political community